Toxicity of deltamethrin to Eriocheir sinensis and the isolation of a deltamethrin-degrading bacterium, Paracoccus sp. P-2. (October 2020) - Ning, Mingxiao; Hao, Wenjing; Cao, Cheng; Xie, Xiaojun; Fan, Weifeng; Huang, Hua; Yue, Yichao; Tang, Mengyue; Wang, Wen; Gu, Wei; Meng, Qingguo
Abstract: Deltamethrin is used widely in Eriocheir sinensis aquaculture to remove wild fish and parasites. The residual deltamethrin greatly affects the growth and quality of E. sinensis . In this study, the LC50 of deltamethrin against E. sinensis at 24, 48 and 96 h was determined to be 6.5, 5.0 and 2.8 μg/L, respectively. The enzyme activity and gene transcription of SOD, CAT, and PO in the hepatopancreas of E. sinensis after deltamethrin stimulation showed an increasing tendency, and these enzymes reached their maximum activities at 6–10 d. The MDA content accumulated with increased time of deltamethrin stress. After 15 d of deltamethrin stress, the hepatopancreas of E. sinensis was found to be damaged based on HE staining. These results showed that deltamethrin is highly toxic to E. sinensis. But the half-life of deltamethrin is long and mainly relies on biodegradation. To resolve the pollution of residual deltamethrin, a strain of deltamethrin-degrading bacteria, P-2, was isolated from the sediment of an E. sinensis culture pond. Through morphological observation, physiological and biochemical identification and 16S rDNA sequence analysis, we found that this strain belonged to Paracoccus sp. When the pH was 7, the substrate concentration was low, the inoculation amount was high, and the deltamethrin degradation effect of Paracoccus sp. P-2 was good. The deltamethrin residue in the hepatopancreas and muscle of E. sinensis decreased significantly when Paracoccus sp. P-2 was added at 6.0 × 10 8 CFU/L. The degradation efficiency of Paracoccus sp. P-2 in the hepatopancreas and muscle was more than 70%. These results showed that Paracoccus sp. P-2, the first deltamethrin-degrading bacterium in aquaculture, could be used to remove residual deltamethrin and improve the food safety of E. sinensis. Highlights: Deltamethrin was highly toxic to Eriocheir sinensis. A deltamethrin degrading strain was selected from the sediment of E. sinensis culture pond and named Paracoccus sp. P-2. When the pH was 7, the inoculation amount was high and the deltamethrin degradation effect of P-2 was good. Paracoccus sp. P-2 can effectively reduce the residues of deltamethrin in E. sinensis hepatopancreas and muscle.